2015
DOI: 10.1101/gr.191759.115
|View full text |Cite
|
Sign up to set email alerts
|

TP53 regulates miRNA association with AGO2 to remodel the miRNA–mRNA interaction network

Abstract: DNA damage activates TP53-regulated surveillance mechanisms that are crucial in suppressing tumorigenesis. TP53 orchestrates these responses directly by transcriptionally modulating genes, including microRNAs (miRNAs), and by regulating miRNA biogenesis through interacting with the DROSHA complex. However, whether the association between miRNAs and AGO2 is regulated following DNA damage is not yet known. Here, we show that, following DNA damage, TP53 interacts with AGO2 to induce or reduce AGO2's association o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 41 publications
(50 reference statements)
2
41
0
1
Order By: Relevance
“…Thus, only a fraction of expressed miRNAs actively target mRNAs. This phenomenon has been observed previously in an AGO‐PAR‐CLIP study of TP53‐dependent miRNA‐AGO2 association in which most miRNAs differentially expressed in the RISC associated with AGO2 did not correspond to relative abundance in total RNA samples . While we do not know why only a relatively small number of total miRNAs are bound to AGO2, we speculate that some miRNAs may compete for binding to AGO2 better than others.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, only a fraction of expressed miRNAs actively target mRNAs. This phenomenon has been observed previously in an AGO‐PAR‐CLIP study of TP53‐dependent miRNA‐AGO2 association in which most miRNAs differentially expressed in the RISC associated with AGO2 did not correspond to relative abundance in total RNA samples . While we do not know why only a relatively small number of total miRNAs are bound to AGO2, we speculate that some miRNAs may compete for binding to AGO2 better than others.…”
Section: Discussionsupporting
confidence: 70%
“…In fact, it is emerging that the association between miRNAs and the RISC complex is a regulated process. As an example, Krell et al 33 . showed that following DNA damage, P53 interacts with AGO-2 to induce or reduce AGO-2’s association with subsets of miRNAs, including multiple let-7 family members.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are involved in most developmental and physiological processes and their deregulation is linked to many human diseases, including cancer (Siomi & Siomi 2010, Krell et al 2015. Several studies have shown that miRNAs can act as both oncogenes and tumour suppressors and expression profiling has associated specific miRNAs with a variety of cancers in the hope of developing tumour subtype-specific signatures (Calin & Croce 2006, Esquela-Kerscher & Slack 2006, Weber et al 2006, Zhang et al 2007.…”
Section: Introductionmentioning
confidence: 99%